PENGARUH STABILITAS MAKROEKONOMI DAN KESEHATAN PERBANKAN TERHADAP PEMBIAYAAN UMKM DI INDONESIA: PENDEKATAN MODEL ARDL - Adinda Maharani; Fathir Moh. Abdillah; Muhammad Caesario Juliansyah; Viola Maulina Susanto; Nazeli Adnan (Jurnal Ekonomi, Manajemen dan Akuntansi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to Indonesia's economy, yet access to financing remains a persistent challenge. This study aims to analyze the effects of macroeconomic stability and banking health on MSME financing in Indonesia, using the Autoregressive Distributed Lag (ARDL) approach. Secondary time-series data covering 2009–2023 were obtained from the Financial Services Authority (OJK), Bank Indonesia, and the Central Statistics Agency (BPS), encompassing variables of inflation, lending interest rate, Capital Adequacy Ratio (CAR), and Non-Performing Loan (NPL). The ARDL Bounds Test confirmed a long-run cointegration relationship among all variables. In the short run, CAR positively and significantly influenced MSME financing, while NPL exerted a negative and significant effect; inflation showed no immediate impact. In the long run, all variables were statistically significant: inflation and lending interest rate negatively affected MSME financing, CAR had a strong positive effect, and NPL acted as a structural constraint on credit expansion. These findings emphasize that sustainable MSME financing in Indonesia depends on both macroeconomic stability and sound banking performance, underscoring the need for coordinated monetary and prudential policies to strengthen MSME credit access